(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The mammary glands undergo significant physiological changes throughout a woman’s life, particularly in response to hormonal fluctuations associated with aging. This article explores the age-related changes in mammary gland structure and function, including developmental stages from puberty through menopause and beyond. It discusses the implications of these changes for breast health, including the risk of benign and malignant conditions. Additionally, the article examines current treatment options available for age-related conditions affecting the mammary glands, including hormonal therapies, surgical interventions, and lifestyle modifications. Understanding these changes is crucial for developing effective strategies for monitoring and treating breast health in aging women.